Memorial days - Brooks, Geraldine (Viking, 2025)
"It was Memorial Day, 2019, when Geraldine Brooks received news that her husband, Tony Horwitz, had collapsed and died, far from home, in the middle of his own book tour. The complex tasks required in the face of such a sudden death left her no time to properly grieve for him. Three years later, still feeling broken and bereft, she booked a flight to a remote island off the coast of Tasmania. Alone on a rugged stretch of coast, she revisited a thirty-five-year marriage filled with risk, adventure, humor, and love. There, she pondered the ways other cultures deal with mourning and finally seized the time and space she needed for her own grief"--Inside jacket flap.